Social function of taxes as a toolkit for income differentiation reduction among population of the depressed republics of the North Caucasus Federal District - H. Aliev, Basir (2020)
In the conditions of a difficult political situation, economic uncertainty and increasing unemployment in the land-poor manpower-surplus, depressive republics of the North Caucasus Federal District, the need to implement the entrepreneurial opportunities of the population is clearly manifested. It seems that small business can manifest itself in these conditions as a separate element of the economy decentralized sector. Of course, the success of small business in a depressed region depends on the state position to a large extent. And this is natural, because only the state is capable of creating the necessary conditions in market relations and various preference provision for the development of entrepreneurship, especially in the mountainous territories of the country.It should be noted that the next economic crisis and pandemic (coronavirus) not only led to the depletion of the state budget, but also collapsed the production activity of small diversified enterprises in the region. Most of the entrepreneurs of the North Caucasus Federal District declare that they are not able to independently solve the complex of this phenomenon negative consequences.